The Noka Theatre : Storytelling as social catalyst : Revitalising the historic Breytenbach Theatre in the old Overzicht Artists Village, Sunnyside, Pretoria - Botes, Nico (University of Pretoria, 2019)
Mini Dissertation (MInt (Prof))--University of Pretoria, 2019.